From Financial Exclusion to Inclusion : Increasing the Availability of Credit to the Urban Poor in Latin America - Gwinner, William Britt; Goldberg, Michael J.; Solo, Tova Maria; Didoni, Alberto (World Bank, Washington, DC, 2012)
This is the second of two articles that draw on the results of recent studies of the links between financial services and low income communities in Latin America. While the focus remains on the nature and inherent costs of financial exclusion for the unbanked -- those without basic deposit and transaction accounts, this article focuses on access to credit and on some of the efforts that have been made to increase the availability of credit services to the urban poor. It closes by describing ways in which World Bank projects could support increased private sector lending for community development, including housing, home improvement, and basic physical and social infrastructure as well as micro and small business lending.